Research On the Accounting Recognition and Measurement Problems of Enterprise Data Assets - Tang, Zhongbao (International Journal of Global Economics and Management, 2024)
The leap from data resource recovery to data asset is not only an important node for the development of digital economy but also an opportunity for the development of new quality productivity. Data assets into data circulation broaden the channel, and optimize the market allocation of data elements by clarifying the boundary of data property rights and reducing data transaction costs. Data assets have not only the universality of assets, but also the particularity of data elements. Clarifying the definition of enterprise data assets is the proper meaning of realizing data value. The three dimensions of "creation-control and transaction" respectively refer to the creation of data property rights through data registration, data intellectual property registration and other ways, the reduction of enterprise data transaction costs through policy formulation and "dynamic control", and the positive circulation of enterprise data circulation by optimizing the data income distribution system. The three dimensions bridge the gap between data rules in different fields, ensure the consistency of data policies, and then break the shackles of data transaction, and give full play to the multiplier effect of data elements.